2019
DOI: 10.1177/0890117119839904
|View full text |Cite
|
Sign up to set email alerts
|

Only 1 in 10 Patients Told to Lose Weight Seek Help From a Health Professional: A Nationally Representative Sample

Abstract: Purpose: Receiving weight loss advice from a health-care provider has been associated with more weight loss efforts and greater odds of achieving weight loss. However, whether patients seek help from their provider or other health professional with weight loss after receiving advice from them to lose weight is largely unknown. Design: Cross-sectional data from the 2011 to 2012 National Health and Nutrition Examination Survey (NHANES). Sample: A total of 3862 overweight/obese adults. Measures: Questionnaires as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…52 Relatedly, a recent study found that only 10.9% of adults with overweight/obesity who were advised to lose weight sought help from health professionals. 53 HCPs also should discuss evidence-based strategies for behaviour change such as self-monitoring, 54 using SMART (specific, measurable, attainable, relevant and timely) goals, 54 and seeking social support 55 for their behaviour change efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Relatedly, a recent study found that only 10.9% of adults with overweight/obesity who were advised to lose weight sought help from health professionals. 53 HCPs also should discuss evidence-based strategies for behaviour change such as self-monitoring, 54 using SMART (specific, measurable, attainable, relevant and timely) goals, 54 and seeking social support 55 for their behaviour change efforts.…”
Section: Discussionmentioning
confidence: 99%
“…52 Relatedly, a recent study found that only 10.9% of adults with overweight/obesity who were advised to lose weight sought help from health professionals. 53 HCPs also should discuss evidence-based strategies for behaviour change such as self-monitoring, 54 using SMART (specific, measurable, attainable, relevant and timely) goals, 54 and seeking social support 55 for their behaviour change efforts. Study findings should be considered in light of study limitations, which include the cross-sectional study design and the use of self-reported data assessing receipt of HCP counselling, reported actions on HCPs' recommendations and PA levels.…”
Section: Open Accessmentioning
confidence: 99%
“…Instead, they preferred self-guided efforts to manage ill health [ 16 ]. Another study reported that approximately 10% of overweight/obese adults sought care from either dieticians/nutritionist, personal trainer or doctors to lose weight [ 17 ]. However, in contrast, persons with obesity or overweight have reported a need of more help with weight management from physicians in primary health care [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While obesity-related chronic diseases are managed within primary and secondary care systems, obesity as a chronic disease is undertreated [ [3] , [4] , [5] , [6] ]. While several provincial medical associations as well as the Canadian Medical Association now recognize obesity as a chronic disease [ 7 ], no provincial or territorial health system has included obesity within their existing chronic disease management frameworks.…”
Section: Introductionmentioning
confidence: 99%